The COSO III audit model, for the health sector in Villavicencio-Meta (Revista "Boletín el Conuco", 2021)
The research seeks to deepen the knowledge of accounting and control from an approach to understand the conception of the internal control system used in Pymes. It is essential to recognize the importance of internal control, which in the case of this research is developed with the components of the COSO III model, in the context of the Pymes in the health sector.The methodology used in the research is developed from a quantitative perspective oriented towards a descriptive approach; the information is obtained and analyzed through checklists and surveys. The purpose of this study is to determine the effectiveness of the internal control implemented in the Pymes of the health sector, from a theoretical approach having as a reference framework the internal control model proposed by COSO III.Keywords: control, internal audit, SME, accounting
Keywords: control; internal audit; SME; accounting